Bilateral rapidly destructive hip disease: a case report and literature review - Yan Shen; Yi Zhang; Jing Fu; Hang Pei; Jiang Hua; Bangjian He (Frontiers in Medicine)
Rapidly destructive hip disease (RDHD) is a rare syndrome marked by swift joint degeneration and substantial functional impairment, typically affecting a single hip joint. The occurrence of bilateral RDHD is exceptionally uncommon, highlighting the urgent need for further research into its pathogenesis, pathological changes, and treatment strategies. We present the case of a 75-year-old female who developed significant bilateral hip mobility limitations and buttock pain 6 months after being diagnosed with mild bilateral hip osteoarthritis. Imaging revealed the disappearance of both femoral heads. After excluding contraindications, the patient successfully underwent left uncemented total hip arthroplasty (THA). Postoperative pathology confirmed the diagnosis, showing degeneration and focal necrosis. This case represents the first documented instance of favorable clinical outcomes following THA in bilateral RDHD.